Cytokine expression in the visceral adipose tissue after laparoscopic and conventional surgery in a rodent model. Issue 1 (December 2016) - Lingohr, Philipp; Dohmen, Jonas; Matthaei, Hanno; Konieczny, Nils; Hoffmann, Juliane; Bölke, Edwin; Wehner, Sven; Kalff, Jörg
Abstract Background Laparoscopic Surgery has become a worldwide standard procedure for a variety of indications. This has been attributed to a milder postoperative inflammatory response by the innate immune system potentially mediated through immune mediators released by the visceral adipose tissue (VAT). However, an in vivo experimental evidence is lacking and is the issue of our present study. Methods Male Wistar rats (N = 24) underwent standardized surgical procedures of conventional cecum resection (CCR), conventional sham operation, laparoscopic cecum resection (LCR), or laparoscopic sham operation. Cytokine expression of leptin, resistin, and IL-6 was analyzed in VAT before and after resection by quantitative RT-PCR. Results Postoperative leptin gene expression was reduced in the CCR and LCR groups, while expression was not significantly affected in both sham groups compared to the preoperative levels. In contrast, IL-6 expression was not affected in the LCR group, but was significantly elevated in the CCR cohort. The IL-6 expression was significantly higher in CCR compared to LCR. Resistin expression levels did not differ between all groups. Conclusions Our study underlines the role of immunological involvement of VAT in the postoperative phase. Low leptin levels seem to act as a stimulator for energy uptake in order to cope with postoperative stress. A lower IL-6 expression in the LCR compared to the CCR group may indicate a weaker inflammatory activity potentially adding to the clinical benefits observed in patients undergoing LS.